High‐Entropy Sulfides as Electrode Materials for Li‐Ion Batteries (Adv. Energy Mater. 8/2022). Issue 8 (24th February 2022) - Lin, Ling; Wang, Kai; Sarkar, Abhishek; Njel, Christian; Karkera, Guruprakash; Wang, Qingsong; Azmi, Raheleh; Fichtner, Maximilian; Hahn, Horst; Schweidler, Simon; Breitung, Ben
Abstract : High Entropy Sulfides In article number 2103090, Simon Schweidler, Ben Breitung and co‐workers synthesize and characterize high‐entropy sulfides with five transition metals in equimolar concentrations, with different M:S ratios by a simple one‐step mechanochemical approach. Two new types of single‐phase high‐entropy sulfides with pyrite (Pa‐3) and orthorhombic (Pnma) structures are obtained and used for the first time as electrode materials for battery applications.